DECORATIVE AND APPLIED ART IN THE LEISURE OF YOUNG PEOPLE (Web of Teachers: Inderscience Research, 2024)
After Uzbekistan gained independence, a new period in the development of crafts began, folk crafts were revived on the basis of market rules. In Uzbekistan, as a result of the privatization of the first line of local industry enterprises, small state-owned enterprises were transformed into private enterprises of artisans, new craft enterprises were opened. The craft began to work not only for the domestic market, but also for export. The organizational form of the craft has also changed: it began to develop in the form of a small family enterprise, self-employment. As a result of the fruitful leisure activities of the youth of Uzbekistan, a special place is occupied by the upbringing of a generation that passes on to the future generation the traditions of our ancestors that benefit the family.